Faktor-Faktor yang Berhubungan dengan Kepemilikan Jamban Sehat di Desa Kerta Dewa Kabupaten Musi Rawas Utara Provinsi Sumatera Selatan - Sonia, Sonia; Hidayati, Fajrina; Reskiaddin, La Ode (Jurnal Kesmas Jambi, 2023)
Abstract Latrines are places where excrement is disposed of to prevent environmental pollution and the spread of disease. Data from the Surulangun Health Center in 2022, shows that Kerta Dewa Village ranks first in open defecation by 54%. The aim of the study was to determine the factors associated with owning healthy latrines in Kerta Dewa Village, North Musi Rawas Regency. Quantitative research with a cross sectional approach. The sample in this study was 89 respondents taken by proportional stratified random sampling. Data were analyzed using the chi-square statistical test. This study found that respondents who did not have healthy latrines were 74.2% and there was a relationship between knowledge (0.000), attitude (0.000), income (0.004), clean water facilities (0.000), role of health workers (0.001) with ownership of healthy latrines in Kerta Dewa Village, North Musi Rawas Regency. Knowledge, attitudes, income, clean water facilities, the role of health workers have a significant relationship with ownership of healthy latrines in Kerta Dewa Village. It is recommended that health workers and the village government optimize the community-based total sanitation program so that the number of healthy latrine owners increases. Keywords: Healthy latrines, income, knowledge, attitudes, clean water.